Wine market trends in the EU and Hungary - Szakál, Zoltán (Acta Agraria Debreceniensis, 2006)
Traditions of the Hungarian grape and wine sector go back centuries. However, although this sector is proud of its rich traditions, it has gone through several shocks. Having joined the EU, Hungary has become a part of the integrated internal market. The commercial obstacles and difficulties among EU-members and Hungary have officially been removed. At the same time, within the Common Agricultural Policy, the wine market has been organised at community level by EU-members. There is no possibility for the sector to access any kind of direct supports from the Hungarian budget, unless such activity is definitely allowed by community directions or unless Hungary were authorized in the framework of a supplementary procedure. After joining the EU, the customs-protection - which aim was to protect the EU-market against the third countries - reduced, so wine producers from overseas countries emerged with their competitive wine prices in the home market and also became competitors of Hungarian wine producers who have been working under low technically equipped conditions. In order to increase the competitiveness of Hungarian wines, it is essential to improve the machinery of producers and to improve the equipment of winecellars. Finally, it is also vital that Hungarian wine producers develop a well-constructed marketing policy.